2014
DOI: 10.3892/ijo.2014.2530
|View full text |Cite
|
Sign up to set email alerts
|

TRAP1 revisited: Novel localizations and functions of a ‘next-generation’ biomarker (Review)

Abstract: In the last decade, the identification and characterization of novel molecular mechanisms and pathways involving the heat shock protein TRAP1/HSP75 in cancers and other diseases enhanced the scientific interest. Recent reports have shown that TRAP1 stays at the crossroad of multiple crucial processes in the onset of neoplastic transformation. In fact, TRAP1: i) contributes to the tumor's switch to aerobic glycolysis through the inhibition of succinate dehydrogenase, the complex II of the mitochondrial respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 48 publications
(56 reference statements)
2
70
0
Order By: Relevance
“…In agreement with a role for TRAP1 outside mitochondria, for quality control of mitochondrial proteins 46 , our findings prompted us to hypothesize that TRAP1 could possibly act as a “controller” of the correct Sho localization at the interface between the ER/mitochondrial compartments.…”
Section: Discussionsupporting
confidence: 77%
“…In agreement with a role for TRAP1 outside mitochondria, for quality control of mitochondrial proteins 46 , our findings prompted us to hypothesize that TRAP1 could possibly act as a “controller” of the correct Sho localization at the interface between the ER/mitochondrial compartments.…”
Section: Discussionsupporting
confidence: 77%
“…The therapeutic selectivity of Hsp90 inhibitors results from the presence of a high-affinity, activated form of Hsp90 in tumours, whereas the Hsp90 in normal tissues is a low-affinity, inactive form [37]. Similarly, TRAP1 has been pursued as a promising target for novel mitochondriotopic/therapeutic strategies for its cytoprotective and antiapoptotic roles in cancer cells [6] and other diseases [38], although recent advances in TRAP1 biology suggest to be prudent [25]. In this article, we have shown that TRAP1 expression also influences tumour cell's migratory potential, which raises new questions to answer in the near future in order to select TRAP1 as predictive biomarker of cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…Recent advances in TRAP1 biology have shown how TRAP1 functions as a network hub protein, involved in all these cellular processes. In fact, TRAP1 i) contributes to the regulation of mitochondrial physiology through an interaction and regulation of respiratory complexes [3][4][5]; ii) is part of a pro-survival signalling pathway aimed at evading the toxic effects of oxidants and anticancer drugs and plays a role in protecting mitochondria against apoptotic stimuli [25]; and iii) controls protein homeostasis through a direct involvement in the regulation of protein synthesis and degradation [2,12,15]. Whether its roles in such processes are uniformly oncogenic or not is now matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…TRAP1 is a HSP90 molecular chaperone upregulated in several human malignancies [5, 6] and, among others, human CRC [7]. High TRAP1 levels have been proposed as prognostic biomarker in this malignancy, being associated with extensive lymph node dissemination [8] and, together with high ERCC1, with poor overall survival (OS) in metastatic disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…TRAP1 regulation of these cell functions depends on the co-translational quality control of specific client proteins and, thus, the modulation of the expression/ubiquitination of a network of proteins [11, 12]. In such a context, we previously suggested that human CRCs with increased TRAP1 expression are characterized by selective upregulation of specific TRAP1 network proteins [6, 13, 20, 21], even though the clinical significance of this regulation is still largely unexplored [6]. Thus, this study was designed to obtain a comprehensive evaluation of the biological and clinical relevance of TRAP1 protein network in human CRC and to address the hypothesis that the coordinated upregulation of TRAP1 and its client proteins may serve as a prognostic signature in metastatic disease.…”
Section: Introductionmentioning
confidence: 99%